Usulan Pengendalian Risiko Keselamatan Dan Kesehatan Kerja Menggunakan Metode HIRARC di PT Buana Niaga Bersama - Priana Dwiansyah; Kusnadi Kusnadi (Jurnal Serambi Engineering, 2023)
PT Buana Niaga Bersama Karawang is a manufacturing company that produces retreaded tires, this company uses mold machines and boiler machines. This study aims to analyze the application of safety and health from the beginning of the production process to finished goods, because this company has not fully implemented occupational safety and health, for example workers do not use safety shoes, carry raw materials manually. This research is a descriptive research that explains the application of occupational safety and health in the production area of PT Buana Niaga Bersama, the method used is HIRARC (Hazard Identification, Risk Assessment and Risk Control) with the first stage namely identifying potential hazards, then evaluating potential hazards and the last stage namely the control of potential hazards. The results of this study are based on the identification of potential hazards, there are 24 cases of potential hazards, with a risk assessment that there are as many as 62% or 15 cases of potential hazards with low risk (low risk), as many as 25% or 6 cases of potential hazards with moderate risk (medium risk). and as many as 13% or 3 cases of potential danger with severe risk (extreme risk). Suggestions for company owners are to provide personal protective equipment and establish standard operating procedures, while for workers, namely to work according to standard operating procedures and use personal protective equipment while working.